Oath-Taking, Peacebuilding and Conflict Resolution in Traditional African Society: The Izzi Example - Kelechi Johnmary Ani; Anselm Aleke Oyon (E-Journal of Religious and Theological Studies)
The reality of human history reveals the age-long traditions of different people in their quest for survival. Over the ages, African men have continued to search for peace and security in their immediate environment. Hence, to ensure that man lives safely and peacefully, the forefathers of different African societies invented the culture of oath-taking as a means of survival. This study thus examined the place of oath-taking in the lives of the Izzi people (a North Eastern Igbo sub-group, in South Eastern, Nigeria). The study drew data from interviews with key informants and also sought information from documents in order to come up with its conclusions. The study revealed that oath-taking was used in resolving conflicts in the Izzi clan. The importance of oath-taking is that it bonds society together and discourages different forms of violent behaviours. The implications became that in that traditional society, there was more peace in the izzi environment due to the peacebuilding contributions of oath-taking. The analysis led to the recommendation that the culture of oath-taking needs to be revived and promoted as a means of peacebuilding in African societies. This is fundamental as it will enhance advanced studies on oath-taking as a peacebuilding strategy that would help in creating a more peaceful society in the global village.